Quantitative trait locus mapping identifies a locus linked to striatal dopamine and points to collagen IV alpha‐6 chain as a novel regulator of striatal axonal branching in mice. (28th September 2021) - Thomas, Mélanie H.; Gui, Yujuan; Garcia, Pierre; Karout, Mona; Gomez Ramos, Borja; Jaeger, Christian; Michelucci, Alessandro; Gaigneaux, Anthoula; Kollmus, Heike; Centeno, Arthur; Schughart, Klaus; Balling, Rudi; et al.
Abstract: Dopaminergic neurons (DA neurons) are controlled by multiple factors, many involved in neurological disease. Parkinson's disease motor symptoms are caused by the demise of nigral DA neurons, leading to loss of striatal dopamine (DA). Here, we measured DA concentration in the dorsal striatum of 32 members of Collaborative Cross (CC) family and their eight founder strains. Striatal DA varied greatly in founders, and differences were highly heritable in the inbred CC progeny. We identified a locus, containing 164 genes, linked to DA concentration in the dorsal striatum on chromosome X. We used RNAseq profiling of the ventral midbrain of two founders with substantial difference in striatal DA–C56BL/6 J and A/J—to highlight potential protein‐coding candidates modulating this trait. Among the five differentially expressed genes within the locus, we found that the gene coding for the collagen IV alpha 6 chain (Col4a6) was expressed nine times less in A/J than in C57BL/6J. Using single cell RNA‐seq data from developing human midbrain, we found that COL4A6 is highly expressed in radial glia‐like cells and neuronal progenitors, indicating a role in neuronal development. Collagen IV alpha‐6 chain (COL4A6) controls axogenesis in simple model organisms. Consistent with these findings, A/J mice had less striatal axonal branching than C57BL/6J mice. We tentatively conclude that DA concentration and axonal branching in dorsal striatum are modulated by COL4A6, possibly during development. Our study shows that genetic mapping based on an easily measured Central Nervous System (CNS) trait, using the CC population, combined with follow‐up observations, can parse heritability of such a trait, and nominate novel functions for commonly expressed proteins. Abstract : QTL mapping with Collaborative Cross strains identifies locus linked to striatal dopamine and points to COL4A6 as modulator of axonal branching in the striatum.